The Impact of Strategic Planning on Growth of Small Businesses in Nigeria. - Babandi Ibrahim Gumel (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose- There is a need to develop a framework that will improve the understandings of business planning and performance and its effects on growth particularly during the stages of small business development. The study attempted to fill in the gap stated. Design - The single case qualitative study relates small business growth with strategic planning where financial performance, market share, sales, and profits or instead return on investment is used to measure the growth. Existing literature fails to establish a concrete relationship between strategic planning and growth of small businesses which indicates a gap in the literature that will help understand the steps of managing the organizational transition of small business growth. Findings - The study fails to establish a significant relationship between formal planning and transitional growth, but instead found the influence of the planning process in communication the owner’s goals, vision, mission, and intentions to both internal and external stakeholders of small businesses. The study influence of the shared vision with customers on making them loyal and advertisers through word of mouth. The study revealed how customers’ word of mouth increased the customer base of small businesses thereby increasing the product demand and eventual expansion of capacity leading to the growth of small businesses. The growth of small businesses will result in an increased reduction in the unemployment rate which will reduce the poverty rate in the Nigerian economy. Practical Implications- Answering the primary and supporting questions will help small business owners to understand how strategic planning is essential in the transitional growth of their businesses.